Testing of bio-rational and synthetic pesticides to manage cabbage aphid (Brevicoryne brassicae L.) in cabbage field at Rampur, Chitwan, Nepal - Nyaupane, Sushil; Tiwari, Sundar; Thapa, Resham Bahadur; Jaishi, Sita (Journal of Agriculture and Natural Resources, 2021)
Cabbage aphid (Brevicoryne brassicae L.) is an important pest of cabbage which reduces the yield and quality of the cabbage head. Farmers haven been using chemical pesticides to manage them but unfortunately these practices are toxic for human health, biodiversity and the environment. The study was conducted to test the efficacy of different bio-rational insecticides along with the chemical insecticide. ‘Green Coronet’ cabbage variety was used and the field experiment was laid out in the experimental farm of Agriculture and Forestry University (AFU), Rampur, Chitwan during the winter season of 2014. The Experiment was designed in randomized complete block design with having 7 treatments (bio-rational insecticides with chemical and control) and 3 replications. Plot size was 5.76 m2 (2.4m×2.4m) and spacing of 1 m was maintained between each blocks and plots. Field experiment showed that the highest reduction of cabbage aphid was obtained in Dimethoate (30 EC) treated plot followed by Derisom treated plot. The highest yield of cabbage head was obtained in Dimethoate treated plots (66.47 mt/ha) which was significantly at par with the Derisom (58.79 mt/ ha) treated plots. The yield for other treated plots were 47.60 mt/ha for Margosom, 43.77 mt/ha for Verticillium, 41.63 mt/ ha for Cow urine, 36.77 mt/ ha for Spinosad and control (33.45 mt/ ha) in terms of cabbage head yield. And, at the same time, natural enemies’ population was significantly lower to Dimethoate treated plots compared to bio-rational insecticides. Thus, Derisom (Derris based botanical) might be the best viable alternative in eco-friendly management of cabbage aphid considering cabbage head yield and protection of natural enemies. It was also evident from the research that Margosom (Neem based botanical) was found beneficial not only to conserve natural enemies in the cabbage field but also to minimize cabbage aphid population.